Why Does Proactive Personality Predict Employee Life Satisfaction and Work Behaviors? A Field Investigation of the Mediating Role of the Self-Concordance Model - GREGURAS, Gary J. (Institutional Knowledge at Singapore Management University, 2010)
We integrated the proactive personality and the self-concordance model literatures to hypothesize and test a model that explicates the processes through which proactive personality relates to employee life satisfaction, in-role performance, and organizational citizenship behaviors (OCBs). Across 3 time periods, data were collected from 165 employees and their supervisors. Results indicated that more proactive individuals were more likely to set self-concordant goals and attain their goals, which in turn predicted psychological need satisfaction. Psychological need satisfaction subsequently predicted employee life satisfaction, in-role performance, and OCBs. Further, goal attainment directly predicted employee life satisfaction. Our results also indicated that proactive personality's relations with employee life satisfaction, in-role performance, and OCBs were entirely indirect through goal self-concordance, goal attainment, and psychological need satisfaction.